Identification of Plasmatic Biomarkers of Foie Gras Qualities in Duck by Metabolomics - Mozduri, Zohre; Marty-Gasset, Nathalie; Lo, Bara; Masoudi, Ali Akbar; Morisson, Mireille; Canlet, Cécile; Arroyo, Julien; Bonnet, Agnès; Bonnefont, Cécile M. D. (Frontiers in Physiology, 2021)
The foie gras is an emblematic product of French gastronomy composed of waterfowl fatty liver. The organoleptic qualities of this product depend on the liver characteristics such as liver weight (LW) and technological yield (TY) at cooking. One of the main issues for producers is to classify the foie gras with high or low technological quality before cooking them. Thus the study aims at identifying biomarkers of these characteristics with non-invasive biomarkers in duck. 1H-NMR (nuclear magnetic resonance of the proton) analyses were performed on plasma of male mule ducks at different time points during the overfeeding period to obtain a large range of liver characteristics so as to identify plasmatic biomarkers of foie gras. We used two methods, one based on bucket data from the 1H-NMR spectra and another one based on the fingerprints of several metabolites. PLS analyses and ANOVAs were performed to identify biomarkers. We identified 18 biomarkers of liver weight and 15 biomarkers of technological yield. As these two quality parameters were strongly correlated (-0.82), 13 biomarkers were common. The lactate was the most important biomarker, the other were mainly amino acids. Contrary to the amino acids, the lactate increased with the liver weight and decreased with the technological yield. We also identified 5 biomarkers specific to LW (3 carbohydrates: glucuronic acid, mannose, sorbitol and 2 amino acids: glutamic acid and methionine) that were negatively correlated to liver weight. It was of main interest to identify 2 biomarkers specific to the technological yield. Contrary to the isovaleric acid, the valine was negatively correlated to the technological yield.